Key Factors Influencing Talent Development of Junior Soccer Players in Sports Academies: A Focus on Coaches and Parents - Bognár József; Kiss Zoltán; Csáki István; Trzaskoma-Bicsérdy Gabriella; Trzaskoma Łukasz; Révész László (Sciendo, 2024)
Soccer academies are responsible for the comprehensive development of young athletes, including formal education, living, and preparation for tournaments. Research on soccer youth development from the perspectives of coaches and parents of sports academy students has been limited. This study aimed to discover their perspectives on the key internal and external factors that influence the development of young soccer talents. Questionnaire data were collected from 79 coaches and 326 parents of U15 to U19 soccer players across eight soccer academies across four Central and Eastern European countries. The questionnaires presented 33 Likert-scale type questions organized around four dimensions to include internal factors, professional/sports factors, family/school factors, and other external factors.